High Prevalence of Triple-Negative Breast Cancer in Southern Shaanxi Province, China - Xing X; Fan Z; Gao Y; Liu Z (Cancer Management and Research, 2021)
Xuemei Xing,1,* Zhigang Fan,2,* Yue Gao,3 Zheng Liu1,3 1Department of Clinical Laboratory, 3201 Hospital, Xi’an Jiaotong University Health Science Center, Hanzhong, Shaanxi, 723000, People’s Republic of China; 2Department of Oncology, 3201 Hospital, Xi’an Jiaotong University Health Science Center, Hanzhong, Shaanxi, 723000, People’s Republic of China; 3College of Medical Laboratory Science, Guilin Medical University, Guilin, Guangxi, 541004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zheng LiuDepartment of Clinical Laboratory, 3201 Hospital, Xi’an Jiaotong University Health Science Center, 783 Tianhan Ave, Hanzhong, Shaanxi, 723000, People’s Republic of ChinaTel/Fax +86 916 2383201Email zliu1111@163.comPurpose: Describing the clinical features of patients with breast cancer in an area is important to provide the information for the local oncologist to make sound treatment plans. In this study, we explored the clinical features of breast cancer patients in Southern Shaanxi Province, China.Patients and Methods: A total of 328 breast cancer patients between 2010 and 2015 were recruited at our hospital. Patients’ clinical information and the results of the histopathological examination were collected. Independent sample t-test and Cox regression were used to analyze the data.Results: The peak age onset of these patients was between 45 and 50. At diagnosis, 8.23% of patients were at clinical stage 1 and 29.57% were triple-negative breast cancer subtype. High expression of Ki-67 in these patients was found associated with triple-negative breast cancer. The 5-year survival rate in these patients was 66.4%, and the survival rate in stage 1 and 2 patients (88.2%) was significantly higher than that in stage 3 and4 (57.4%).Conclusion: We here reported the clinical features of patients with breast cancer in Southern Shaanxi Province, China. The breast cancer patients in Southern Shaanxi Province showed a unique clinical feature.Keywords: 5-year survival rate, breast cancer, clinical features, triple-negative breast cancer